High modulus polyimide particle-reinforcement of epoxy composites. Issue 7 (15th February 2021) - Essmeister, Johannes; Taublaender, M. Josef; Koch, Thomas; Cerrón-Infantes, D. Alonso; Unterlass, Miriam M.; Konegger, Thomas
Abstract : A novel class of fully organic composite materials with well-balanced mechanical properties and improved thermal stability was developed by incorporating highly crystalline, hydrothermally synthesized polyimide microparticles into an epoxy matrix. Abstract : In this work, a novel class of fully organic, lightweight composite materials was prepared by incorporating highly crystalline, hydrothermally synthesized poly( p -phenylene pyromellitimide) (PPPI) microparticles into a commercial epoxy matrix. Particle loadings of up to 15 vol% could be achieved. Microstructural, mechanical, and thermal properties of these composites were investigated by scanning electron microscopy, three-point bending and Vickers hardness testing, dynamic mechanical analysis, nanoindentation, and thermogravimetric analysis. The incorporation of the PPPI filler particles into the epoxy matrix was found to be homogeneous. Powder X-ray diffraction shows that PPPI's crystallinity is retained in the composites, and infrared spectroscopy indicates a covalent bonding of PPPI to the epoxy matrix. Flexural modulus and storage modulus were increased by the PPPI addition, while the flexural strain at break was reduced. In contrast to that, the flexural strength remained unaffected by the incorporation of PPPI filler particles. Raising the filler content also resulted in an improvement of hardness. Furthermore, a decrease in glass-transition temperature with increasing PPPI content was observed, as well as a pronounced increase in thermal stability of the composites in comparison to the unfilled cured epoxy resin. These results indicate the high potential of this new class of composites with prospective applicability e.g. in the fields of sports equipment, aerospace, and automotive technology.